RETRACTED: Case report: Coronavirus Disease 2019 (COVID-19) modified RNA vaccination-induced Adult-Onset Still's Disease with fulminant myocarditis as initial presentation - Zhou, Mi; Wong, Chun Ka; Yeung, Wan Yin Winnie; Siu, Chung Wah; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2023)
Myocarditis is a rare complication of Coronavirus Disease 2019 (COVID-19) vaccination. We report a case of an elderly female who presented initially with acute myocarditis, fulminant heart failure, and atrial fibrillation after receiving a modified ribonucleic acid (mRNA) vaccine (BNT162b2). Unlike other patients with vaccine-induced myocarditis, she developed persistent fever, sore throat, polyarthralgia, diffuse macular rash, and lymphadenopathy. After extensive investigation, she was diagnosed with post-vaccination Adult-Onset Still's Disease. The systemic inflammation gradually subsided after the use of non-steroidal anti-inflammatory drugs and systemic steroids. She was discharged from hospital with stable hemodynamics. Methotrexate was subsequently given to maintain long-term remission.